Ograniczenia ekstrakcji częstotliwości podstawowej dźwięku fortepianu w oparciu o analizę cepstrum = Limit the extraction of fundamental frequency sound of the piano based on cepstrum analysis - Rajs, Arkadiusz; Rajs, Katarzyna (Journal of Education, Health and Sport, 2017)
Rajs Arkadiusz, Rajs Katarzyna. Ograniczenia ekstrakcji częstotliwości podstawowej dźwięku fortepianu w oparciu o analizę cepstrum = Limit the extraction of fundamental frequency sound of the piano based on cepstrum analysis. Journal of Education, Health and Sport. 2016;6(11):305-310. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167140 http://ojs.ukw.edu.pl/index.php/johs/article/view/3997 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 17.11.2016. Ograniczenia ekstrakcji częstotliwości podstawowej dźwięku fortepianu w oparciu o analizę cepstrum Limit the extraction of fundamental frequency sound of the piano based on cepstrum analysis dr inż. Arkadiusz Rajs Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckich w Bydgoszczy, Wydział Telekomunikacji, Informatyki i Elektrotechniki, Zakład Teletransmisji, Al. Prof. S. Kaliskiego 7, 85-790 Bydgoszcz, arajs@utp.edu.pl. dr hab. Katarzyna Rajs, prof. nadzw. Akademia Muzyczna im. Feliksa Nowowiejskiego w Bydgoszczy ul. Słowackiego 7, 85-008 Bydgoszcz, k.rajs@wp.pl Abstrakt Artykuł ten opisuje sposób wykorzystania algorytmu ekstrakcji częstotliwości podstawowej sygnału opartego na analizie cepstrum do określenia wysokości pojedynczych dźwięków instrumentów muzycznych, a dokładniej - dźwięku fortepianu. Przedstawia szczegółowo tą metodę oraz wskazuje problemy związane z dokładnością tego algorytmu dla różnych wysokości dźwięku. Abstract This article describes how to use the algorithm for the extraction of fundamental frequency signal based on cepstrum analysis to determine the amount of the individual sounds of musical instruments, and more-the sound of the piano. Shows in detail the method and indicates problems with the accuracy of this algorithm for various. Słowa kluczowe: analiza cepstrum, przetwarzanie sygnałów Key words: cepstrum analysis, signal processing